Bovine Adenovirus-3 pVIII Suppresses Cap-Dependent mRNA Translation Possibly by Interfering with the Recruitment of DDX3 and Translation Initiation Factors to the mRNA Cap - Ayalew, Lisanework E.; Patel, Amrutlal K.; Gaba, Amit; Islam, Azharul; Tikoo, Suresh K. (Frontiers in Microbiology, 2016)
Earlier, targeting of DDX3 by few viral proteins has defined its role in mRNA transport and induction of interferon production. This study was conducted to investigate the function of bovine adenovirus (BAdV)-3 pVIII during virus infection. Here, we provided evidence regarding involvement of DDX3 in cap dependent cellular mRNA translation and demonstrated that targeting of DDX3 by adenovirus protein VIII interfered with cap-dependent mRNA translation function of DDX3 in virus infected cells. Adenovirus late protein pVIII interacted with DDX3 in transfected and BAdV-3 infected cells. pVIII inhibited capped mRNA translation in-vitro and in-vivo by limiting the amount of DDX3 and eIF3. Diminished amount of DDX3 and eIFs including eIF3, eIF4E, eIF4G and PABP were present in cap binding complex in BAdV-3 infected or pVIII transfected cells with no trace of pVIII in cap binding complex. The total amount of eIFs appeared similar in uninfected or infected cells as BAdV-3 did not appear to degrade eIFs. The co-immunoprecipitation experiments indicated the absence of direct interaction between pVIII and eIF3, eIF4E or PABP. These data indicate that interaction of pVIII with DDX3 interferes with the binding of eIF3, eIF4E and PABP to the 5’ Cap. We conclude that DDX3 promotes cap-dependent cellular mRNA translation and BAdV-3 pVIII inhibits translation of capped cellular mRNA possibly by interfering with the recruitment of eIFs to the capped cellular mRNA.